2021
DOI: 10.3389/fcimb.2021.577236
|View full text |Cite
|
Sign up to set email alerts
|

Review: Effect of Gut Microbiota and Its Metabolite SCFAs on Radiation-Induced Intestinal Injury

Abstract: Gut microbiota is regarded as the second human genome and forgotten organ, which is symbiotic with the human host and cannot live and exist alone. The gut microbiota performs multiple physiological functions and plays a pivotal role in host health and intestinal homeostasis. However, the gut microbiota can always be affected by various factors and among them, it is radiotherapy that results in gut microbiota 12dysbiosis and it is often embodied in a decrease in the abundance and diversity of gut microbiota, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 124 publications
(140 reference statements)
5
41
0
Order By: Relevance
“…There are multitudes of evidence revealing that a close correlation exists between intestinal microbes and the productive performance of poultry [ 13 , 14 ]. Short-chain fatty acids (SCFAs) are deemed as one of the richest metabolites of intestinal microorganisms and effectively regulate the microbial balance and maintain the stability of the internal environment [ 15 ]. Nevertheless, there remain rare reports on the effects of sodium butyrate supplementation on the cecal microbiota and metabolites of laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…There are multitudes of evidence revealing that a close correlation exists between intestinal microbes and the productive performance of poultry [ 13 , 14 ]. Short-chain fatty acids (SCFAs) are deemed as one of the richest metabolites of intestinal microorganisms and effectively regulate the microbial balance and maintain the stability of the internal environment [ 15 ]. Nevertheless, there remain rare reports on the effects of sodium butyrate supplementation on the cecal microbiota and metabolites of laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the pathogenesis of RIII remains unknown, but it is believed that the combined effects of epithelial injury, vascular changes, microbial and immune factors lead to severe radiation enteropathy (Hauer-Jensen et al, 2014; Li et al, 2021). The gut microbiota plays an important role in maintaining intestinal barrier function, regulating immune homeostasis and protecting intestinal repair mechanisms (Ahlawat et al, 2021; Gasaly et al, 2021; Touchefeu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There were a large number of TUNEL + cells in the crypts and villi in WAI group compared to the CON group, and EGCG+WAI group significantly decreased the apoptosis levels in the small intestine (Figure 3f). Alkaline phosphatase (ALP) is an endogenous enzyme and plays an important role in maintaining the integrity of intestinal epithelial cells (He et al, 2021;Sheng et al, 2021). At 3.5 days after WAI, ALP was lost from the jejunal (Figure 3g), the permeability of epithelial cells increased, causing increasingly expression of inflammatory factors (Figure 3h-j) (Lallès, 2019).…”
Section: Egcg Promotes Proliferation and Survival Of Intestinal Stem ...mentioning
confidence: 99%
“…Acetic acid accounts for the highest proportion of short-chain fatty acids produced by intestinal bacteria. It can adjust the pH value of the intestinal tract to allow beneficial bacteria to survive, prevent harmful bacteria, and help maintain the stability of the intestinal environment [27]. Furthermore, studies have confirmed that SCFAs have important research significance for NAFLD [28].…”
Section: Cosm Could Increase the Levels Of Acetic Acid Propionic Acid...mentioning
confidence: 99%